USE OF MODERN TECHNICAL TOOLS IN TEACHING INFORMATICS AND INFORMATION TECHNOLOGIES (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
This article is about the relevance of the issue of using modern tools in education, how modern technical tools of teaching can be used in the continuous education system.